Peningkatan Kapasitas Wali Murid TK dalam Implementasi Menu Gizi Seimbang dalam Kaitannya dengan Perkembangan Kognitif Anak di TK Melati Indah, Pekanbaru, Riau - Joni, Joni; Alim, Melvi; Puspita, Yenda; Hastriati, Ade Yelda (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to enhance the capacity of parents at TK Melati Indah, Pekanbaru, in implementing balanced nutrition based on local food to address early childhood obesity and unhealthy lunch box patterns. The method was conducted in four stages: identification and pre-testing, interactive education on